(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The study was conducted to evaluate the efficacy of four botanical oils viz., neem, castor, black cumin and sesame against Spodoptera frugiperda in the laboratory during the period from November 2021 to March 2022. Tween-20 as an emulsifier was used with the tested oils at 5, 7.5 and 10% concentration along with an untreated control were evaluated for their toxic effect against S. frugiperda. The botanical oils gave profound toxic effect against eggs, first, second and third instar larvae of S. frugiperda. Each dose of different oils showed 100% inhibition of egg hatching and caused mortality of first instar larvae. Castor oil at 10% concentration gave the highest mortality (32.22 and 30.00%) while sesame oil at 5% showed the lowest (11.11 and 10.00%) against second and third instars larvae, respectively. Castor oil performed the highest toxicity of LD50 values against second (2015.8 mg kg-1) and third (3525.5 mg kg-1) instars larvae. Conversely, sesame oil performed the lowest toxicity of LD50 values against second (8391.3 mg kg-1) and third (15222.3 mg kg-1) instars larvae after 72 hours of exposure. Castor oil might be used as ovicidal and larvicidal ingredients against S. frugiperda. Bangladesh J. Agril. Res. 48(3): 371-383, September 2023